Recesso contratual e o exercício inadmissível de posição jurídica - Cañada, Eduardo Gomes (Universidade de São Paulo, 2023)
O direito civil admite a extinção voluntária e unilateral de certas relações contratuais. A esse fenômeno genericamente considerado pode ser dado o nome de recesso contratual, ou em vernáculo, denúncia e resilição. Subjacente a esse nome há três espécies de negócios unilaterais, com tipicidade quanto aos pressupostos, efeitos e meios de controle do direito potestativo que os fundamenta. A hipótese é a de que o abuso do direito (ou exercício inadmissível de posição jurídica, na figura parcelar do venire contra factum prorium, por intermédio da boa-fé) é o meio de correção de injustiças que escapam aos esquemas tipicizantes do exercício de poderes de acordo com a ideia intermediária de espécies de recesso. A noção de inadmissibilidade é semanticamente aberta e decorre da impossibilidade da lei ou dos negócios jurídicos regularem todos os comportamentos possíveis dos sujeitos de direito, demandando um juízo corretivo preter legem. Porém, essa delimitação é consequência, primeiramente, dos fundamentos, pressupostos e do exercício regular do negócio de recesso (em seus respectivos tipos). Em seguida, é possível analisar a abusividade do recesso em três frentes possíveis e apresentar as depurações dogmáticas que a proibição do venire contra factum proprium pode oferecer para a solução dos casos concretos. The Civil Law allows the voluntary and unilateral termination of certain contractual relationships. This phenomenon can generically be called recesso, or denunciation and resiliation. Underlying this name, there are three types of unilateral acts, typical in terms of the premises, effects and means of controlling the potestative right on which they are based. The hypothesis is that the abuse of the right (or the inadmissible exercise of a legal position, in the partial figure of venire contra factum prorium, through good faith) is the means of correcting injustices that escape the typical schemes of the exercise of powers according to the intermediate idea of species of recesso. The notion of inadmissibility is semantically open and stems from the impossibility of the law or legal transactions regulating all the possible behavior of the subjects of law, requiring a preter legem corrective judgment. However, this delimitation is a consequence, firstly, of the foundations and premises and the regular exercise of the terminations act (in their respective types). It is then possible to analyze the abusiveness of withdrawal on three possible fronts and present the dogmatic perfectioning that the prohibition of venire contra factum proprium can offer for the solution of specific cases.
Keywords: Abuse of rights; Abuso do direito; Boa-fé; Contract; Contrato; Good faith; Recesso; Termination

Critical analysis of the institutional framework governing the agreement establishing the African Continental Free Trade Area - Lehlongwa, Thulane Charlo (Stellenbosch University, 2023)
The African Continental Free Trade Area as a flagship project of Agenda 2063 represents renewed attempts by the African Union to drive the continent closer to its economic integration ambitions, which can be formally traced back to the adoption of the African Declaration on Cooperation, Development, and Economic Independence, and later the Treaty Establishing the African Economic Community. Building on these frameworks, the AfCFTA seeks to, amongst others, advance intra-African trade by creating a single market for goods and services facilitated by the movement of persons, promoting sustainable and inclusive socio-economic growth, creating a liberalised market for goods and services, and promoting industrial development. Central to the attainment of the objectives of the AfCFTA is a well-functioning and effective institutional framework at a continental, regional, and national level all well-integrated to facilitate and oversee its implementation. The strengthening of regional and continental institutions to effectively lead and drive Africa’s transformation agenda has also been recognised by Agenda 2063 as a key enabler to this end. The demise of previous African integration efforts has mainly been attributed to the weakness of regional and continental organs to be able to effectively oversee and administer the implementation of continental programmes by the countries. This thesis appraises the institutional framework established to oversee the implementation, administration, facilitation, and monitoring of the AfCFTA, and this is considered against the broader African Union institutional framework and the regional economic communities. Although vastly different, the thesis further considers the experience and best practices from the European Union regional integration model to draw lessons and with a view to reforming and integrating African continental and regional bodies to be able to effectively oversee key initiatives including the AfCFTA. Finally, the thesis considers some of the work already initiated by the AU to review and reconfigure the extant continental bodies and then recommends some key interventions to reinforce and better integrate the institutional framework of the AfCFTA with the existing continental and regional frameworks.
Keywords: AfCFTA; African Continental Free Trade Area; Dispute resolution; Economic integration; Free Trade; International economic relations

Essai sur les justifications et les flexibilités du droit des brevets - Tanguay, Danoé (Université de Montréal, 2023)
Ce mémoire porte sur l’usage particulier des flexibilités du droit des brevets en matière de technologies vertes. Bien que les études empiriques concernant les effets du droit des brevets sur l’innovation en matière de technologies vertes soient peu nombreuses et que les effets du droit des brevets sur l’innovation en général soient incertains, la justification du brevet comme incitatif à l’innovation semble encadrer les réflexions sur l’usage des flexibilités du droit des brevets. Ce constat nous sert de porte d’entrée pour explorer la relation évolutive des justifications et des flexibilités du droit des brevets. Dans un premier temps, nous étudions l’évolution du droit des brevets, en mettant l’accent sur comment il a été justifié et comment les premiers régimes étaient modulés en fonction du contexte social dans lequel ils s’inscrivaient. Dans un second temps, nous observons l’influence de la justification dominante du droit des brevets, soit la fonction d’incitatif à l’innovation, sur l’interprétation des flexibilités prévues dans l’Accord sur les ADPIC et le discours les concernant. Cette étude met en lumière que les mêmes justifications ont fondé des régimes différents, notamment dans l’espace accordé aux flexibilités, et montre que cette place a été restreinte au fil du temps. Nous concluons en avançant que l’étude de l’usage des flexibilités des brevets en matière de technologies vertes reste à ses débuts. Plus d’études empiriques sur le sujet sont nécessaires et celles-ci doivent entrer en dialogue avec les fonctions autres du droit des brevets que celle de l’incitatif à l’innovation.
Keywords: Accord sur les ADPIC; Brevets; Droit de la propriété intellectuelle; Flexibilités du droit des brevets; Histoire du droit de la propriété intellectuelle; Intellectual property; Intellectual property law; Justifications du droit des brevets; Justifications of patent law; Patent law flexibilities; Patents; TRIPs

Patente, mercado e abuso: considerações a partir das patentes de medicamentos - Inácio, Gabriel Felipe Nami (Universidade de São Paulo, 2023)
Este trabalho buscou investigar as dimensões das patentes no mercado, sobretudo no âmbito de medicamentos essenciais, à luz de suas funções socioeconômica e concorrencial. O problema que se buscou investigar é o seguinte: quais são os possíveis impactos das patentes de medicamentos no mercado? A hipótese explorada foi a de que as patentes de medicamentos podem servir de instrumentos de consolidação de poder econômico na medida em que podem se prestar a moldar a estrutura de mercado e, com isso, contribuir para um cenário de desequilíbrio de poder econômico e um mercado tendente à concentração. Para que essa hipótese pudesse ser explorada, foi preciso, primeiro, investigar as premissas estruturais das patentes, com o intuito de verificar a natureza jurídica do instituto, os requisitos de patenteamento e de que forma a proteção das patentes aos medicamentos foram fruto de uma opção política internacional. Na sequência, investigou-se as principais funções que as patentes exercem, notadamente a função social, econômica e concorrencial. Indispensável, nesse ponto, foi traçar a correlação entre as funções das patentes, especialmente a função concorrencial, e o interesse público. A partir disso, foi possível perceber que as patentes de medicamentos essenciais podem moldar a estrutura de mercado e, embora tenham claras limitações e devam servir ao interesse público, podem gerar custos informacionais, de acesso e de inovação, sendo passíveis de criarem distorções de mercado que podem inviabilizar o acesso à saúde. As patentes e esses custos apresentam direta relação com o desenvolvimento econômico. Em razão disso, é preciso que o exercício do direito de patente (que não é e tampouco deve ser considerado abusivo per se) seja analisado à luz do cumprimento das funções socioeconômica e concorrencial que exercem. É preciso, ainda, avaliar em que medida os custos que esse exercício produz suplantariam os benefícios sociais decorrentes da tecnologia patenteada. A partir dessas investigações, observou-se que a legislação atual conta com alguns mecanismos que visam dar cumprimento a essas funções, como é o caso do abuso de direito e da licença compulsória. O abuso de direito mediante o exercício das patentes pode ser classificado de acordo com o grau dos interesses envolvidos, o que influencia diretamente na consequência e no remédio a ser utilizado. Observou-se, também, que o abuso de patente se desenvolveu de tal modo que se tornou, inclusive, estratégia de defesa, como é o caso da chamada patent misuse. Por sua vez, o licenciamento compulsório se apresenta como uma solução temporariamente eficaz, muito embora historicamente o uso do licenciamento compulsória tenha ocorrido timidamente. Estes instrumentos, contudo, não são suficientes, de forma que a criação de alternativas que, a um só tempo, viabilizem o acesso à saúde e criam outros incentivos ao investimento em P&D por parte dos agentes econômicos se afigura essencial. This paper sought to investigate the dimensions of patents in the market, especially in the field of essential medicines, in the light of their socio-economic and competitive functions. The problem we sought to investigate is the following: what are the possible impacts of drug patents on the market? The hypothesis explored was that drug patents can serve as instruments for consolidating economic power insofar as they can be used to shape the structure of the market and thus contribute to a scenario of unbalanced economic power and a market tending towards concentration. In order to explore this hypothesis, it was first necessary to investigate the structural premises of patents, to verify the legal nature of the institute, the patenting requirements and how the protection of patents on medicines was the result of an international political choice. Next, the main functions that patents perform were investigated, particularly their social, economic, and competitive functions. At this point, it was essential to analyze the correlation between the functions of patents, especially the competitive function, and the public interest. From this, it was possible to see that patents on essential medicines can shape the market structure and, although they have clear limitations and should serve the public interest, they can generate informational, access and innovation costs, which can create market distortions that can make access to health unfeasible. Patents and these costs are directly related to economic development. For this reason, the exercise of patent rights (which are not and should not be considered abusive per se) must be analyzed in the light of the fulfillment of their socio-economic and competitive functions. It is also necessary to assess the extent to which the costs produced by this exercise outweigh the social benefits derived from the patented technology. Based on these investigations, it was observed that current legislation has some mechanisms aimed at fulfilling these functions, such as the abuse of rights and compulsory licensing. The abuse of rights through the exercise of patents can be classified according to the degree of the interests involved, which directly influences the consequence and the remedy to be used. It was also observed that patent abuse has developed to such an extent that it has even become a defense strategy, such as patent misuse. For its part, compulsory licensing appears to be a temporarily effective solution, although historically the use of compulsory licensing has been timid. These instruments, however, are not enough, so the creation of alternatives that, at the same time, enable access to health and create other incentives for investment in R&D by economic agents is essential.
Keywords: ABUSO DE PODER ECONÔMICO; Abuse of economic power; Abuse of power; Abuso de poder; Industrial property; Market; Medicamentos; Medicine; Mercado; Patentes; Patents; Propriedade industrial

The impact of exchange platforms on the security of European markets - D'Alessandro, Francesco (LUISS Guido Carli, 2023)
Exchange platforms listed on European markets: financial contamination? The Luna collapse: present-day exposé. Aògorithmic stablecoins. The Luna project and the Terra ecosystem. Legal framework of a billion-dollar scam. Class action lawsuits. National and European implications of such actions. Misleading advertising (binance's liability) and culpa in eligendo. Exchange platforms listed on European markets: financial contamination? Parallels between shares and cryptocurrency investments: lack of transparency giving rise to bubbles. InvestVoyager case study. FTX case study. Positive law and new horizons. DeFi self-regulation: AML compliance and exchange platforms. The proposal of MiCA regulation (markets in crypto-assets). Payment systems directive 2 (PSD2). Directive 2009/110/EC on e-money. Potential solutions (proposals). External audit of smart contracts: a comprehensive examination-technical and legal perspectives. Digital euro. Establishment of a national or European commission: risks for consumers and comparative research. Regulation of exchanges and enforcement of transparency obligations.

Le statut juridique du marchand en droit camerounais et en droit québécois - Akoumou Ndjomo, Jeanne Laure (Université de Montréal, 2023)
Ce mémoire analyse la place juridique du marchand dans les sociétés camerounaise et québécoise. Le droit a toujours cherché à catalyser les activités des marchands en régulant l’accès à leur profession, en contrôlant leurs activités et en leur imposant de nombreuses obligations. La préoccupation des législateurs québécois et camerounais vis-à-vis de l’entité qu’est le marchand est palpable, les nombreuses lois mises sur pied pour encadrer ce personnage en témoignent. Le droit camerounais et le droit québécois abordent le sujet du marchand de façon différente. Nous verrons que dans l’appellation et dans le régime applicable à cette entité, le législateur québécois et son homologue camerounais se retrouvent la majorité du temps aux antipodes l’un de l’autre, mais il arrive parfois que leurs règles présentent des similitudes. Les nombreuses règles mises en place par les législateurs pour réguler les actions du marchand vont nous amener à examiner l’importance que ce dernier a au sein de la société. Conscients du pouvoir que le marchand peut avoir, les législateurs n’ont-ils pas fixé un grand nombre de règles par peur que ce dernier abuse de ce pouvoir ? Cette interrogation nous mènera au dernier volet de ce mémoire qui consistera à analyser les rapports de forces entre le marchand et les consommateurs premièrement, et entre le marchand et l’État en seconde place. L’intérêt de cette recherche est en premier lieu juridique évidemment. En effet, au cours de notre étude, nous verrons des notions telles que la commercialité et ses éléments constitutifs et nous ouvrirons le débat sur son utilité et sa désuétude. Nous aborderons également le rôle joué par le commerçant dans le processus de globalisation du droit et la création d’un droit post-moderne. En plus d’avoir un intérêt juridique, ce sujet révèle également un intérêt socio-économique car il nous amènera à aborder la notion de « commerçant de fait », une entité apparue à cause de la précarité économique et sociale à laquelle la majorité des pays africains fait face. This study analyzes the legal place of the merchant in Cameroonian and Quebec societies. The law has always sought to catalyze the activities of merchants by regulating access to their profession, controlling their activities and imposing numerous obligations on them. The concern of Quebecer and Cameroonian legislators concerning the merchant is palpable, the large number of laws put in place to regulate this character testify to it. Cameroonian law and Quebec law approach the subject of the merchant in different ways. We will see that in the calling and in the regime applicable to this entity, the Quebecer legislator and its Cameroonian counterpart find themselves most of the time at opposite ends, but sometimes it happens that their rules present similarities. The rules put in place by legislators to regulate the actions of the merchant will lead us to examine the importance that the latter has within society. Aware of the power that the merchant can have, haven't the legislators set a large number of rules for fear that the latter will abuse this power? This question will lead us to the last part of this study which will consist in analyzing the balance of power between the merchant and the consumers first, and between the merchant and the State in second place. The interest of this research is obviously primarily legal. Indeed, during our study, we will see notions such as commerciality and its constituent elements and we will open the debate on its usefulness and its obsolescence. We will also discuss the role played by the merchant in the process of globalization of law and the creation of post-modern law. In addition to having a legal interest, this subject also reveals a socio-economic interest because it will lead us to approach the notion of "commerçant de fait", an entity that appeared because of the economic and social precariousness to which the majority of Africans countries faces.
Keywords: Cameroonian law; Commerçant; Consommateur; Consumer; Corporate Social Responsibility; Droit camerounais; Droit post-moderne; Droit québécois; Globalisation du droit; Globalization of law; Marchand; Merchant; Notion d'entreprise; Notion of enterprise; Post-modern law; Quebec law; Responsabilité sociale des entreprises; Theory of commerciality; Théorie de la commercialité; Trader

توحيد قواعد قانون التجارة الدولية في إطار المنظمات الدولية الحكومية - حواس, عشوي; محند, زايد (جامعة مولود معمري تيزي وزو, 2023)
يتطلب توحيد قواعد قانون التجارة الدولية جهودا ووسائل معتبرة، الأمر الذي جعل المنظمات الدولية الحكومية هي التي تتكفّل بهذه المهمّة. وتنقسم هذه المنظمات الدولية الحكومية إلى منظمات دولية عالمية، ومنظمات دولية إقليمية. اتبعت هذه الأخيرة أساليب متعددة للتوحيد، من اتفاقيات دولية وقوانين نموذجية وقوانين موحّدة. وأمام تعدّد أساليب التوحيد هذه، يجب اختيار الأسلوب الأكثر ملاءمة لضمان فعّالية عملية التوحيد. لكن، رغم الجهود المبذولة من قبل هذه المنظمات، فإنها لم تصل إلى التوحيد الكلّي لهذه القواعد، وذلك بسبب اختلاف الأنظمة السياسية والاجتماعية للدول، فلم يشمل التوحيد إلاّ بعض مجالات القانون. كما بقيت القواعد الموحدة صعبة التطبيق لاختلاف تفسيرها من جهة، ولقلّة خبرة القضاة والمحكّمين في هذا المجال من جهة أخرى. L'unification des règles du droit du commerce international nécessite des efforts et des moyens considérables, ce pourquoi cette tâche a été confiée aux organisations gouvernementales internationales. Ces organisations intergouvernementales sont divisées en organisations internationales mondiales et organisations internationales régionales.Ces dernières ont suivi de multiples méthodes d’unification, notamment des accords internationaux, des lois types et des lois unifiées.Face à ces multiples méthodes d’unification, il faut choisir la méthode laplus appropriée pour garantir l’efficacité du processus d’unification. Cependant, malgré les efforts déployés par ces organisations, elles ne sont pas parvenues à une unification complète de ces règles, en raison des différences entre les systèmes politiques et sociaux des pays. L'unification n'a porté que sur certains domaines du droit. Les règles unifiées restent également difficiles à appliquer en raison de leurs interprétations différentes d'une part, et du manque d'expérience des juges et des arbitres dans ce domaine, d'autre part.

O impacto da Convenção das Nações Unidas sobre Contratos para Venda Internacional de Mercadorias (CISG) nas empresas portuguesas: aplicação e cláusula de opt-out. - Domingues, Ana Rita Pereira (Universidade do Porto, 2023)
A cada um dos vários Estados que compõem a comunidade internacional; corresponde um sistema jurídico, económico, político e social único e próprio. É possível identificar semelhanças, mas também diferenças entre cada um deles. O fenómeno da globalização estabelece cada vez mais pontos de ligação entre o panorama jurídico económico dos países que promovem as transações internacionais e que contactam diretamente com as consequências da globalização. Assim, destaca-se a importância do conceito de “multilateralidade” quando nos referimos a contratos e/ou convenções internacionais e do qual a Convenção de Viena (nome pelo qual a CISG é também conhecida), é exemplo e objeto do presente estudo. A presente dissertação junta as áreas do Direito e Economia Internacionais na análise da Convenção da Nações Unidas sobre Contratos para Venda Internacional de Mercadorias (CISG) e do seu impacto nos processos de internacionalização das empresas portuguesas. Tendo a CISG entrado em vigor em Portugal no dia 1 de outubro de 2021, em plena situação pandémica, pretende-se perceber se as empresas portuguesas têm conhecimento deste novo regime jurídico, se o mesmo está a ser aplicado, ou se as empresas optaram por afastar a sua aplicação, ao abrigo da cláusula de opt-out, que a Convenção prevê no seu artigo 6º.
Keywords: Aplicação; CISG; Comércio; Contratos; Empresas; Internacionalização; Mercadorias; Multilateralidade; Opt-out; Transação internacional

Les baux commerciaux à l'épreuve des circonstances exceptionnelles : cas du covid-19 - Ayinon, Alida (Université Grenoble Alpes, 2023)
Notre étude consistera à explorer les différents mécanismes à envisager par les locataires pour faire face à leur obligation de paiement des loyers commerciaux pendant la crise, partant bien sûr du droit covid-1911au droit traditionnel ou existant avant ladite crise. Il est à noter ici que les mesures prises par le gouvernement français dans la gestion de la crise n’ont pas eu pour vocation dans la majorité des cas de se substituer au droit existant, tel est le cas du droit des contrats. Les deux régimes étant complémentaires, en absence de réponse de l’un, l’on peut se tourner vers l’autre. Il convient de rappeler également qu’une analyse théorique ou générale du régime du bail commercial ne sera pas nécessaire car l’objectif poursuivi par ce sujet est d’examiner la règlementation législative, jurisprudentielle voire doctrinale en matière de bail commercial pendant la crise sanitaire afin de cerner leurs enjeux sur le paiement des loyers commerciaux.
Keywords: Baux commerciaux; COVID-19; Droit des affaires

Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

التجارة الالكترونية بين الواقع والتحديات في الجزائر في ظل تطور استخدام تكنولوجيا المعلومات والاتصال - بغداد, عبد القادر; بن زيدان, الحاج (Ibn Khaldun University of Tiaret, 2023)
تهدف دراستنا الى التعرف على ظاهرة التجارة الالكترونية التي اصبحت حقيقة واقعية انتشرت بصورة كبيرة في وقت قصير، مع إيضاح مكانة التجارة الالكترونية في الجزائر مع تحديد و معرفة أهم التحديات والعوائق التي تواجه الجزائر في استخدام هذه التجارة. رغم ما ذكر آنفا ، نجد ان الجزائر قطعت شوطا كبيرا في تبنيها لهذه التجارة الحديثة ، فقد اتخذت مؤخرا إجراءات عدة في جميع الميادين بغية تدعيم استخدام التقنيات الحديثة ومسايرة التحولات التكنولوجية من اجل تبني التجارة الالكترونية وتذليل العقبات ووضع استراتيجيات وسياسات وطنية للتقدم العلمي والتأهيل المؤسساتي والقانوني من اجل النهوض بالاقتصاد الوطني . توصلت الدراسة الى ان ضعف تمويل التجارة الالكترونية يفرض على الجزائر تشجيع مساهمة القطاع الخاص والمشترك في تمويل هذه التجارة ، تكييف القواعد القانونية الحالية وهذا ما يمثل الهدف الأساسي للقانون 18-05 المتعلق بالتجارة الالكترونية ، الذي سمح بضمان أمن التجارة الالكترونية ، مما يسمح بتنشيط وتحفيز المؤسسات لاقتحام هذا النشاط والارتقاء بمستوى التعاملات التجارية الالكترونية Our study aims to identify the phenomenon of E-commerce , which has become a realistic reality and has spread widely in a short time, with an explanation of the status of E-commerce in Algeria, while identifying and knowing the most important challenges and obstacles facing Algeria in the use of this trade. Despite what was mentioned above, we find that Algeria has come a long way in adopting this modern trade. It has recently taken several measures in all fields in order to support the use of modern technologies and keep pace with technological transformations in order to adopt E-commerce and overcome obstacles and develop national strategies and policies for scientific progress and institutional and legal rehabilitation from for the advancement of the national economy. The study concluded that the weakness of financing E-commerce requires Algeria to encourage the contribution of the private sector and the participant in financing this trade, adapting the current legal rules, and this represents the main objective of Law 18-05 related to E-commerce , which allowed ensuring the security of E-commerce, which allows stimulating and stimulating institutions To break into this activity and raise the level of electronic commercial transactions.
Keywords: Commerce électronique; Enjeux du commerce électronique en Algérie; Paiement électronique; Technologies de l'information et de la communication; التجارة الإلكترونية; الدفع الالكتروني; تحديات التجارة الالكترونية في الجزائر; تكنولوجيا المعلومات والاتصالات

أساس المسؤولية الجزائية لجرائم الشركات التجارية - دحو, خديجة; دهلي, حبيبة (Ibn Khaldun University of Tiaret, 2023)
مسؤولية الشركات التجارية في الجانب الجنائي هي مفهوم قانوني يحدد امكانية مساءلة الشركات او المؤسسات التجارية جنائيا عن الجرائم التي ترتكب في اطار أنشطتها. تاريخيا كان يتم ملاحقة ومساءلة الأفراد جنائيا فقط عن افعالهم الاجرامية ومع طفرة قانون الأعمال وتزايد الوعي بضرورة مساءلة الشركات اصبحت مسؤولية الشركات التجارية جزائيا واقعا في العديد من البلدان. Corporate criminal liability is a legal concept that determines the possibility of holding corporations or commercial entities criminally accountable for crimes committed within the scope of their activities. Historically, only individuals were pursued and held criminally responsible for their criminal actions. However, with the evolution of business law and increased awareness of the need to hold corporations accountable, corporate criminal liability has become a reality in many countries Corporate criminal liability is based on the principle that a corporation can be considered an independent entity separate from its directors, employees, and shareholders. Therefore, if a criminal offense is committed within the company's operations, it can be prosecuted and tried independently of the individuals associated with it. The specific criminal offenses for which corporations can be held accountable vary according to national legislation, but they typically include acts such as fraud, bribery, money laundering, tax evasion, environmental violations, human rights abuses, forgery, unfair competition, and others. When a corporation is criminally prosecuted, it can face severe penalties, including hefty fines, asset seizure, dissolution of the
Keywords: Droit des sociétés commerciales; Personnes morales; Responsabilité pénale; الشخصية الاعتبارية; الشركات التجارية; المسؤولية الجنائية

تبني البنوك التجارية التقليدية للمعاملات المصرفية الإسلامية - زرفاط, خليدة; سوالمي, رحاب نور الهدى (جامعة ابن خلدون-تيارت, 2023)
تمثل البنوك التجارية الجزائرية المعبر الرئيسي للوساطة المالية والمصرفية في الاقتصاد الوطني، إذ تساهم بشكل كبير في أغلب المعاملات الاقتصادية داخل وخارج الوطن، وبالتالي فهي تساهم بعدة أدوار مهمة في التنمية الاقتصادية واستدامتها عبر الأجيال، قام ت الحكومة بإنشاء فروع ونواف ذ إسلامية للمعاملات المالية الإسلامية على مستوى هذه البنوك وطرح منتجات مصرفية إسلامية قرر ساعد على جذب المتعاملين بالسوق الموازية لضخ أموالهم بالبنوك الوطنية واستخدامها بصيغ تطبق احكام الشريعة الإسلامية، تعمل الصيرفة الإسلامية على نبذ الربا وتعزيز التكافل الاجتماعي والعدالة. إن استخدام مثل هذه الخدمات يهدف إلى تحقيق المشاركة في الأرباح والخسائر بين البنوك والزبائن. وفي دراستنا تبين لنا مدى تبني البنوك التقليدية الجزائرية للمعاملات المالية الإسلامية من خلال فتح نوافذ إسلامية تعمل وفق الشريعة الإسلامية لتحقيق رضا وإستقطاب الزبائن Algerian commercial banks represent the main catalyst for financial and banking intermediation in the national economy. They to contribute significantly the majority of economic transactions within and outside the country. Consequently, they play several crucial roles in economic development and its sustainability across generations. The government has established branches and windows for Islamic financial transactions in these banks and introduced Islamic banking products. This decision has helped attract participants in the parallel market to channel their funds into national banks and utilize them in accordance with Islamic law principles. Islamic banking aims to eliminate usury (riba) and promote social solidarity and justice. The use of such services aims to achieve profit and loss sharing between banks and customers. Our study has revealed the extent to which Algerian traditional banks have embraced Islamic financial transactions by opening Islamic windows that operate in accordance with Islamic law, aiming to achieve customer satisfaction and attract clients
Keywords: Commercial banks; Customer satisfaction; Financial transactions; Islamic Banking; Islamic windows

تحديات فرض الضرائب على معاملات التجارة الإلكترونية في الجزائر - مبخوت, رفيق; غول, حسين (Ibn Khaldun University of Tiaret, 2023)
لقد تطرّقنا في موضوع دراستنا على تحدّيات فرض الضّرائب على معاملات التّجارة الإلكترونية باعتبار موضوع التّجارة الإلكترونية من المواضيع الهامّة التي تلقى اهتماما كبيرا من قبل الكثير من الباحثين لما لها من انعكاسات على اقتصاديات دول العالم المتقدّمة والنّامية، حيث تعدّ إحدى النّظم الحديثة في إتمام وتنفيذ المعاملات التّجارية عبر شبكات الأنترنت. ولقد أسفرت دراستنا الميدانية في المركز الجواري للضّرائب دائرة السّوقر التي واجهت عدّة صعوبات لإخضاع المعاملات الإلكترونية بسب غياب قوانين والتّشريعات المتعلّقة بتنظيم الضّريبة الإلكترونية وغياب رقمنة القطاع وصعوبات تقنية تطبيق هذا النّوع من الضّرائب. هذا ما أوجب على الجزائر بذل مجهوداتها من أجل دعم وإرساء البنية التحتية للاتّصالات ومسايرة التّقدّم التّكنولوجي في العالم وتسليط الضّوء على القوانين والتّشريعات الجبائية الخاصّة بهذه التّجارة وسَنّها والعمل بها على أرض الواقع. In the subject of our study, we have addressed the challenges of imposing taxes on electronic commerce transactions, considering the issue of electronic commerce as one of the important topics that receive great attention by many researchers because of its implications for the economies of the developed and developing countries of the world, as it is one of the modern systems in the completion and implementation of commercial transactions. Via internet networks. Our field study resulted in the neighborhood tax center, in Sougueur Department, which faced several difficulties in subjecting electronic transactions due to the absence of laws and legislation related to the organization of electronic taxation, the absence of digitization of the sector, and the technical difficulties of applying this type of taxation. This is what required Algeria to exert its efforts to support and establish the telecommunications infrastructure, keep pace with the technological progress in the world, shed light on the laws and fiscal legislation related to this trade, enact them and implement them on the ground.
Keywords: Algeria; Algérie; Commerce électronique; Fiscalité; Internet; Taxe électronique; الأنترنت; التجارة الإلكترونية; الضريبة الإلكترونية; النظام الضريبي

حماية الغير في الشركات التجارية - محوز, العالية; سليمان, عائشة (Ibn Khaldun University of Tiaret, 2023)
تحتل حماية الغير المتعامل مع الشركات التجارية مكانة مهمة في القانون التجاري حيث كرس لها المشرع العديد من الأحكام والمبادئ القانونية التي تساهم في إستقرار المعاملات التجارية للشركات التجارية من جهة، والتي تدعم الثقة في معاملات الشركة مع محيطها الخارجي من جهة أخرى، وذلك نظرا للدور الذي يؤديه الغير في تطوير و إزدهار الشركة وتشجيع المتعاملين للإستثمار في هذا القطاع الاقتصادي المهم. قام المشرع بخطوات مهمة جعل من خلالها الغير يتدخل في حياة الشركة ونشاطها وذلك تخفيفا لآثار إعتبار هذا الغير عضوا خارجيا لا علم له بما يجري داخل الشركة التجارية، لكن تبني المشرع لأنظمة قانونية من أجل الغير لا يعني بلوغ النصوص القانونية هدفها الذي قررت من أجله . The protection of third parties dealing with commercial companies occupies an important place in the commercial law, as the legislator devoted many legal provisions and principles to it that contribute to the stability of commercial transactions of commercial companies on the one hand, and that support confidence in the company’s transactions with its external environment on the other hand, due to the role it plays Others contribute to the development and prosperity of the company and encourage customers to invest in this important economic sector. The legislator took important steps through which he made third parties interfere in the life and activity of the company in order to mitigate the effects of considering this third party as an external member who has no knowledge of what is going on inside the commercial company, but the legislator’s adoption of legal systems for the sake of third parties does not mean that the legal texts have reached their goal for which they were decided

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

O sistema de regulamentação contabilística e o relato financeiro na Guiné-Bissau - Candé, Mamadú (Instituto Politécnico de Santarém, 2023)
Esta dissertação analisa a evolução do sistema contabilístico da Guiné-Bissau, nomeadamente o processo de convergência do Sistema de Contabilidade da Organização para Harmonização do Direito dos Negócios em África (SYSCOHADA) com as normas internacionais de relato financeiro (NIRF). Pretende-se perceber em que medida os laços políticos e culturais influenciaram este processo de convergência no país, e ainda as ligações entre as dimensões culturais, sociais, económicas e financeiras, assim como as respetivas influências na fiscalidade, no ensino e na formação profissional, na organização da profissão contabilística, com base na classificação dos sistemas contabilísticos de Nobes (1998). A Guiné-Bissau é um país membro da Organização para Harmonização dos Negócios em África (OHADA), entidade responsável por edificar e oficializar as normas contabilísticas, que são aprovados através de ato uniforme que envolve dezassete países africanos, o que explica que seja influenciado ou influencie outros países membros daquela organização. Esta investigação contribui para a literatura no domínio da contabilidade e relato financeiro no continente africano, em geral, área ainda pouco explorada e pouco conhecida da comunidade académica, e da Guiné-Bissau, em particular, país independente desde 1973, depois de um período de vários séculos de existência como antiga colónia portuguesa.
Keywords: Contabilidade; Guiné-Bissau; ORNATOC; Relato financeiro; SYSCOA; SYSCOHADA; Sistema contabilístico; Técnicos Oficiais de Contas

UNCITRAL model law on electronic transferable records e prospettive di applicazione - Ambrosino, Alessia (LUISS Guido Carli, 2023)
UNCITRAL model law on electronic transferable records. Dalle esperienze precedenti all’approvazione della MLETR. Lo scopo e la struttura. Le disposizioni sul principio di equivalenza funzionale. Lo standard generale di affidabilità. Altre disposizioni sull’uso degli electronic transferable records. L’applicazione della model law. La necessità di una riforma: l’esperienza del Regno Unito. Trade documents. Possession problem e i “gateway criteria”. Impact assessment dell’electronic trade documents bill. La necessità di adeguare la legislazione italiana.

The protection of EU technological sovereignty in the area of foreign direct investments: legal challenges after the EU regulation 452/2019 - Vecchio, Giuseppe (LUISS Guido Carli, 2023)
EU’s competence over FDI: European technological sovereignty. Definition, origins, and scope of EU foreign investment law. EU competence over foreign direct investments. European technological sovereignty. Regulation 452/2019–screening mechanisms in national legislation with a focus of the Italian regime. Structure of regulation 452/2019. Implementation in national legislation. The screening regulation as a tool to enforce technological sovereignty. EU technological sovereignty in practice. First and second annual report on the screening of foreign direct investments into the Union. A first appraisal of the problematic interplay between FDIs and technological sovereignty.

Holding multinational corporations liable for their transnational environmental harms : a search for global liability - Roxburgh, Craig (Stellenbosch University, 2023)
For several decades, environmentalists have raised the alarm regarding the impending environmental catastrophe that results from the Anthropocene. Much attention has been given to the role that States play in contributing to ecological damage being wrought upon the Earth. However, we have only looked at the environmental destruction perpetrated by multinational companies (“MNCs”) in the past decade. Natural disasters like the Deepwater Horizon explosion have placed MNCs' dangerous impact on the environment in sharp relief. At the same time, revelations in the Carbon Majors Report and global litigation quantify the damage MNCs cause to the environment. Multinational companies (“MNCs), as a result of globalisation and trade liberalisation, are powerful entities within the global economy. Despite their size, MNCs remain primarily unregulated in international human rights law. Debates regarding who bears the duty for human rights intersect with a battle of political will between the Global North and Global South for developing binding human rights duties for MNCs. As a result, they can commit environmental harm, especially in the Global South, with relative impunity due to a lack of effective liability mechanisms. The doctrine of separate legal personality creates specific issues for holding MNCs liable for environmental harms in the Global South. Domestic courts in home States struggle to exercise jurisdiction over the environmental harms MNCs commit. In contrast, systemic barriers in host States create situations where victims are unable to seek redress within their State. To address these concerns, this thesis proposes a global liability regime founded on the principle of integrated regulation. This regime will utilise regulation at the institutional, national and international levels to enforce the environmental obligations of MNCs, rooted in the right to a healthy environment. This gives rise to multiple intersection human rights obligations which will regulate the behaviour of MNCs. This thesis recognises that such a framework requires a drastic reform in how the law and companies are conceptualised. However, such a reform would have wide-reaching implications for vindicating human rights violations.
Keywords: Corporations; Developing countries; Environmental law; Environmental protection; International business enterprises; International cooperation; Liability for environmental damages; Offenses against the environment

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

Integración de los solvencia por medios externos. Análisis de la doctrina y jurisprudencia - Acosta Plaza, José Marcos (Universidad Internacional de Andalucía, 2023)
Trabajo Fin de Máster en Auditoria Operativa, Supervisión Continua, Contabilidad y Control de Subvenciones y Contratos. Tutor: Dr. D. Francisco Javier Maraver Risco. El concepto de operador económico recogido en el artículo 2 , apartado 1, punto 10, de la Directiva 2014/24 debe debe de ser interpretado dentro de una concepción amplia (con distintas variantes) que supera el concepto formal de contratista y las opciones de sumar mediante Uniones Temporales de Empresa o acudiendo a la subcontratación.Tal interpretación es conforme con el objetivo de abrir los contratos públicos a la competencia más amplia posible que persiguen las Directivas en esta materia, en beneficio no sólo de los operadores económicos, sino también de los poderes adjudicadores. Vinculado a esta idea, en virtud del artículo 75 de la LCSP, todo operador económico que se presente a una licitación podrá acreditar la solvencia con medios externos independientemente de los vínculos existentes entre las empresas, ya se tratan empresas de un mismo grupo empresarial o empresas que no tengan vínculos societarios, para acreditar esta solvencia es preciso la aportación de un compromiso ( libertad de forma) en el que se haga referencia al contrato concreto al que se presta la solvencia y en el que se manifieste la puesta a disposición a favor del licitador de los medios de solvencia durante toda la ejecución del contrato, pudiendo ser integrada con medios externos cualquier tipo de solvencia ya sea económica-financiera o técnico- profesional no siendo preciso disponer de un mínimo de solvencia propia pudiéndose integrar toda ella por medios externos.

Les conséquences du changement climatique sur la solvabilité des compagnies d’assurance - Amimar, Clément (Université Lille 2, 2023)

Essor de l'aviation d'affaires : gestion et traitement sur les petites escales aéroportuaires françaises - Barbe, Emma (Aix-Marseille Université, 2023)

L'évolution du régime juridique des fonds marins: les enjeux environnementaux face à la perspective d’une exploitation minière - Bremaud, Coline (Aix-Marseille Université, 2023)
Depuis quelques années, la protection des Océans est au cœur des préoccupations de la communauté internationale. Le nouvel accord BBNJ adopté au mois de juin 2023 en est la dernière manifestation. L’autorité internationale des fonds marins, malgré un retard, est aussi en train de compléter son code minier avec une réglementation sur l’exploitation des minéraux marins. A travers de nombreuses études scientifiques, il a été reconnu que les grands fonds marins abritent une grande diversité d’habitats et d’espèces encore très peu connus. Néanmoins, de nombreuses lacunes, insuffisances et incertitudes persistent quant aux deux régimes en construction. De nombreux acteurs de la communauté internationale manifestent leurs inquiétudes et des voix de tous horizons plaident pour l’établissement d’un moratoire ou « d’une pause de précaution » sur les activités minières dans les grands fonds marins. D’autres voix à l’inverse, soutiennent une solution alternative, celle d’un temps plus long afin de ne pas adopter le projet de manière précipitée. Les questions de la clause des deux ans et du sort des demandes de plans de travail déposées avant l’adoption du projet sont actuellement discutées au sein de l’organisation. Pour résumer, l’Autorité internationale des fonds marins se trouve donc dans une position délicate, celle d’élaborer un droit d’anticipation pour des activités à venir, sans avoir toutes les données scientifiques pour élaborer le régime. Cette étude a donc pour volonté de mesurer les lacunes du droit en construction, ainsi que les solutions pertinentes pour y remédier afin de protéger l’environnement des fonds marins de la perspective de l’exploitation minière.
Keywords: Autorité internationale des fonds marins; BBNJ; Clause des deux ans; Droit maritime; Exploitation minière; Fonds sous-marins; Moratoire; Protection de l’environnement

La fin de non-recevoir de l'article L. 133-3 du Code de commerce - Bresson, Nicolas (Aix-Marseille Université, 2023)

La digitalisation du marché du Lloyd's - Dantec, Rémi (Aix-Marseille Université, 2023)

Faire commun dans une société coopérative et participative autogérée : la nécessité d’accords autour de la volonté collective - Defrance, Hugues (Université de Grenoble, 2023)
Ce mémoire de recherche porte sur l’observation de la mise en place d’un principes supérieur commun qui permet à une société coopérative d’avoir une existence propre en dépassant la somme des intérêts individuels. Cette existence propre permet l’expression d’une organisation autogérée. Pour réaliser cette observation, le cadre des « économies de la grandeur » développé par Luc Boltanski et Laurent Thévenot permet à travers les grilles d’analyse proposée dans leur ouvrage sur « De la justification » de définir dans quels principes supérieur communs se construisent les accords permettant l’expérimentation de cette organisation autogérée. Cette observation à été faite au sein d’une SCOP qui se réclame de cette forme d’organisation et la méthodologie employée est une analyse de discours. Cette observation permet de confirmer que le principe de la volonté collective attaché au modèle de la cité civique est le principe supérieur commun qui anime ce projet collectif autogéré.

L’assurance des risques de guerre dans le transport de marchandises par voie maritime - Forges, Grégoire (Université de Lille, 2023)

L'apport de la convention du Cap et de son protocole aéronautique dans le développement des financements internationaux portant sur des matériels d'équipements aéronautiques - Gachon, Nicolas (Aix-Marseille Université, 2023)

Intégration Euro-Méditerranéenne : enjeux juridiques et contractuels de la construction et de l'exploitation de la connexion fixe ferroviaire au Détroit de Gibraltar - Laaroussi, Mohamed (Aix-Marseille Université, 2023)

Représentant en douane enregistré - Leroy, Julia (Aix-Marseille Université, 2023)

Les navires d'Etat et navires de guerre - Marzolf, Ilona (Aix-Marseille Université, 2023)

Critical Review of the Adoption of the Uncitral Model Law on International Commercial Arbitration in Africa - Mboya, Rachael A. (University of Nairobi, 2023)

Valorisation de l'expérience dans la formation des pilotes de ligne en France - Morel, Sébastien (Aix-Marseille Université, 2023)

L’encadrement juridique de la médiation dans l’espace OHADA : analyse critique de l’acte uniforme relatif à la médiation - Mukuamu, Prince (Université de Sherbrooke, 2023)
Aujourd'hui plus qu'hier, la médiation suscite l’intérêt tant des chercheurs, des praticiens, que des politiques. Cet intérêt se matérialise notamment par les différents cadres juridiques dont elle bénéficie dans plusieurs législations. Afin de promouvoir la médiation au sein de ses États membres, L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a adopté le 23 novembre 2017 un Acte Uniforme relatif à la Médiation (AUM). Après avoir adopté depuis plus de deux décennies un Acte uniforme sur l’arbitrage, l’organisation régionale confirme sa volonté de promouvoir les modes alternatifs de règlement de conflits dans le domaine du droit des affaires. Cependant, l’AUM est un instrument juridique particulier attendu qu'il est le premier de son genre à s’appliquer également aux domaines non encore régis par le droit OHADA. Toutefois, si la médiation tend à se développer de plus en plus, il convient de prendre garde à ce que cette évolution, notamment en ce qui concerne son encadrement légal, ne conduise pas à sa dénaturation. Voilà l’un des défis auquel est également soumis le législateur OHADA.
Keywords: AUM; Acte uniforme; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; OHADA

The concept of separate legal personality in South African company law: A critical examination of its origins, developments and current application - Myeni, Siphosethu (University of KwaZulu-Natal, 2023)
Section 19(1) of the current Companies Act 71 of 2008 states that once a company is incorporated in accordance with this Act, it is considered as a juristic person and exists indefinitely until its name is removed from the companies register. It exists independently from its shareholders and controllers. This effect grants the company with characteristics of a natural person. This analogy implies complete independence of the company. However, this concept finds refuge from the English legal system and was later adopted by South African company law. This notion provides some legal protection to businesses and shields their owners from personal liability for the company's debts and commitments. Companies can use this to enter new markets, reduce their taxes, and take advantage of advantageous business environments. Furthermore, this doctrine promotes joint ventures and partnerships among enterprises from many countries, allowing them to share resources and risks. As a result, this allows international enterprises to benefit by conducting international transactions, expanding abroad, and entering contracts in foreign countries. However, like any other concept, it is susceptible to abuse. Individuals take advantage of it to benefit themselves. This is detrimental to the significance of this doctrine. This dissertation aims to look deeply into this concept, by examining its origins and influence throughout the years and during its current application in the South African legal framework and highlight instances where this doctrine will be set aside. This will be conducted by fully analysing Salomon’s case and the influence it has over current company law. More importantly, the author will further examine the significance of this doctrine in modern company law. This will be done by testing the application of this doctrine to modern corporations and challenges they face.

La mobilité aérienne urbaine : utopie ou réalité - Parisot, Romain (Aix-Marseille Université, 2023)

Les navires autonomes - Perreau, Emilie (Aix-Marseille Université, 2023)

Alliances maritimes : évolution et avenir - Pucciarelli, Clélia (Aix-Marseille Université, 2023)

Anti-Money laundering developments : A comparative appraisal - Schlebusch, Maria Elizabeth (Marlize) (University of Pretoria, 2023)
The objective of this study is to understand and explore the rapid pace at which ML has evolved and the global and local impact thereof.

The law applicable to an international commercial contract : a comparative study of private international law of contract in South Africa and South Korea - Setlhabi, Godiraona (University of Johannesburg, 2023)
Please refer to full text to view abstract.

La grande plaisance face aux sanctions internationales - Stratigéas, Loris (Aix-Marseille Université, 2023)
L’invasion de l’Ukraine par la Fédération de Russie le 24 février 2022 marque l’application de régimes de sanctions internationales économiques et financières aux navires de grande plaisance. Ce mémoire prétend décrire ces différents régimes de sanctions et expliquer avec une approche critique que l’application de certains régimes de sanctions aux navires de grande plaisance peut être remise en cause. Les mesures de gel et leur pendant (l’interdiction de mise à disposition de fonds ou de ressources économiques au profit de la personne ou entité sanctionnée) ont vocation à inciter un changement de comportement auprès de leur cible. Ainsi, cette étude vise également à montrer l’efficacité relative des mesures de gel de navires de grande plaisance dans la poursuite de cet objectif. The invasion of Ukraine by the Russian Federation on 24 February 2022 marks the application of international economic and financial sanctions to yachts. The subject aims to describe these different sanctions regimes and to explain critically that the application of some of them to yachts may be called into question. The freezing measures and their counterpart (the prohibition on making funds or economic resources available to the sanctioned person or entity) are intended to encourage a change in the behaviour of their target. This study therefore also aims to show the relative effectiveness of measures to freeze yachts in achieving this objective.
Keywords: Economic sanctions; Financial sanctions; International sanctions; Mesures restrictives de gel; Navires de grande plaisance; Restrictive freezing measures; Sanctions financières; Sanctions internationales; Sanctions économiques; Yachts

Choke point maritime : entre grands enjeux et risques majeurs - Urquizar, Andréa (Aix-Marseille Université, 2023)
Les choke-points maritimes sont des passages vitaux du commerce mondial empruntés chaque jour par un nombre impressionnant de navires. Bien que ces passages soient les piliers de nos routes maritimes, ils sont pourtant largement méconnus du grand public, mais aussi des acteurs du monde maritime. Ancré dans la mondialisation, beaucoup ne les résume qu’à de simples lieux de passages, or ils sont des artères économiques aux multiples facettes. Générateur de grands enjeux financier et diplomatique, ils présentent également des risques importants pour la navigation, tels que la piraterie ou le trafic d'armes. Enfin il est nécessaire le développement de routes alternatives pour soulager ces passages saturés par le trafic mondial, sans oublier la protection des océans et des espèces vivantes. Maritime chokepoints are vital passages in world trade, used every day by an impressive number of ships. Although these passages are the pillars of our maritime routes, they are largely unknown to the general public, as well as to those involved in the maritime world. Anchored in globalization, many people think of them as mere transit points, yet they are multi-faceted economic arteries. Generating major financial and diplomatic stakes, they also present major risks for shipping, such as piracy and arms trafficking. Last but not least, alternative routes need to be developed to relieve these passages, which are saturated by global traffic, not to mention the protection of oceans and living species.
Keywords: Choke-points; Commerce maritime; Maritime trade

تأسيس شركات المساهمة في التشريع الجزائري - يعقوبي, محمد (Ibn Khaldun University of Tiaret, 2023)
شركة المساهمة هي شركة أموال، لا يقل عدد شركائها عن سبعة شركاء يسمون بالمساهمين تتمثل حصصهم في الشركة بأسهم متساوية القيمة سهلة التداول لا يسأل هؤلاء عن ديون الشركة الا في حدود قيمة الأسهم التي اكتتبوا فيها، وكأي شركة وجب توفر الأركان الموضوعية العامة والخاصة والشكلية وإذا اختلف أحد هذه الأركان يعرضها للبطلان إما نسبي أو مطلق. وضع المشرع الجزائري طريقتين لتأسيس شركة المساهمة إما باللجوء العلني للادخار أو بدون اللجوء العلني للادخار أو بما يعرف بالتأسيس الفوري وتتميز المرحلتين بإجراءات معقدة، يقوم المؤسسون في كلتي المرحلتين بإعداد القانون الأساسي عن طريق جمعية عامة تأسيسية والمصادقة على الشروط المتفق عليها ووضع الشركة للجمهور قصد الاكتتاب فيها إذا ما لجأ المؤسسون لطريقة اللجوء العلني للادخار . أخيرا تسجيل الشركة في السجل التجاري كخطوة أخيرة من مراحل تأسيس الشركة. وأي مخالفة من شأنها تعطيل السير الحسن لتأسيس الشركة يعرضها للبطلان وتعدا المشرع البطلان إلا قيام مسؤولية مدنية وجزائية بتسليط عقوبات رادعة في حق المتخاذلين والمتعمدين في إفشال مشروع الشركة. A joint stock company is a company of funds, the number of its partners is not less than seven partners called shareholders whose shares in the company are represented by shares of equal value easy to trade, these are not responsible for the company's debts except within the limits of the value of the shares in which they subscribed, and like any company, we must provide the general, private and formal pillars, and if one of these pillars differs, it exposes it to invalidity, either relative or absolute. The Algerian legislator has developed two ways to establish a joint stock company, either by public resort to savings or without public resort to saving, or what is known as immediate incorporation, and the two stages are characterized by complex procedures, the founders in both stages prepare the basic law through a constituent general assembly, ratify the agreed terms and place the company for the public in order to subscribe to it if the founders resort to the method of public resort to savings, so that the company is finally registered in the commercial register as a final step of the company's establishment Any violation that may disrupt the proper functioning of the establishment of the com-pany exposes the company to invalidity and the legislator transgresses the nullity, except for civil and criminal liability to impose deterrent penalties against the negligent and deliberate in thwarting the company's project
Keywords: Création d'entreprise; Socitété par action; الإدخار; الإكتتاب